PENGGUNAAN METODE CARD SHORT UNTUK MENINGKATKAN HASIL BELAJAR IPS TEMA 1 ORGAN GERAK HEWAN DAN MANUSIA - Safiudin, Safiudin (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2022)
The purpose in this study is "To Improve IPS Learning Outcomes Theme 1 Animal and Human Movement Organs Through The Card Sort Method of Students of Class V of State Elementary School 2 Tongkuno". The subjects in this study were all 21 students of Class V of Tongkuno State Elementary School 2, consisting of 11 male students and 10 female students. This type of research is Class Action Research (PTK) using action implementation procedures, where research is divided into two cycles. In the first cycle, one meeting was conducted using the Card Sort learning method and the second cycle was carried out as many as one meeting with the same learning method. Based on the results of research that lasted for two cycles, it can be known that the implementation of learning using the Card Sort method in class V of SD Negeri 2 Tongkuno can improve IPS learning outcomes. Where seen in cycle I the average value obtained is 70.23 with a percentage of classical completion of 57.14% and in cycle II increased with an average value of 85.14 with a percentage of classical completion of 90.48%. For this reason, it can be concluded that by using the Card Sort method , the theme of 1 Animal and Human Movement Organs can improve the learning outcomes of IPS students in class V of State Elementary School 2 Tongkuno.